2019
DOI: 10.1002/adfm.201900918
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric, Photoelectric, and Photovoltaic Performance of Silver Niobate Ceramics

Abstract: Ferroelectrics coupled with solar energy conversion are receiving intensive research interest. However, most ferroelectrics with a large remnant polarization can only harvest ultraviolet light in the solar spectrum. Herein, high-quality silver niobate (AgNbO 3 ) ceramics prepared by spark plasma sintering is reported with a bandgap of ≈2.75 eV and a long tail absorption until 800 nm, leading to outstanding photoelectric properties featured by the visiblelight response over 550 nm. Instantaneous photoresponse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…[1] The APV effect widely exists in ferroelectric semiconductor materials, including barium titanate (BTO), [2,3] lead zirconate titanate (PZT), [4,5] and silver niobate (AgNbO 3 ). [6] This phenomenon derives from excited electrons spanning the impurity level to the conduction band due to the interaction between phonons and electrons. In this phenomenon, electrons can be excited by light illumination, resulting in a stable photocurrent in an external circuit.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The APV effect widely exists in ferroelectric semiconductor materials, including barium titanate (BTO), [2,3] lead zirconate titanate (PZT), [4,5] and silver niobate (AgNbO 3 ). [6] This phenomenon derives from excited electrons spanning the impurity level to the conduction band due to the interaction between phonons and electrons. In this phenomenon, electrons can be excited by light illumination, resulting in a stable photocurrent in an external circuit.…”
Section: Introductionmentioning
confidence: 99%
“…A planar ferroelectric device based on AgNbO 3 ceramic with a broad light absorption until 800 nm and a remarkable PV property under visible-light illumination. [38] Figure 4e exhibits the configuration of the prepared device, and the photocurrent enhances the light intensity and the photo-induced signals with a fast response, possessing great potential application of solar scavenging and optical detection. Tao Li and co-workers found that UV irradiation MoS 2 film can make polarization direction initially up polarization direction of BaTiO 3 film down inside, [39] for originally downward BTO film did not affect the polarization direction, light caused internal exciton MoS 2 film production, makes the positive charge accumulation at the interfaces and induced polarization direction from vertical to the vertical downward BTO.…”
Section: Typical Design For Solar Energy Scavengingmentioning
confidence: 99%
“…e) Photoelectric device based on AgNbO 3 ceramics. Reproduced with permission [38]. Copyright 2019, Wiley-VCH.…”
mentioning
confidence: 99%
“…Additionally, Zhao et al also found that lead-free AgNbO 3 ceramics showed a characteristic antiferroelectric double hysteresis loop at a low electric field of 13 kV/mm and a high W rec of 1.6 J/cm 3 at 14 kV/mm was achieved [16]. This finding has triggered a burst of research activities on AgNbO 3 ceramics [54][55][56][57][58][59][60][61][62][63][64]. Among them, Luo et al reported that Ag 0.91 Sm 0.03 NbO 3 (ASN) sample showed excellent energy storage performance (W rec = 5.2 J/cm 3 and η = 68.5%) [64].…”
Section: Introductionmentioning
confidence: 98%